Ambulatory Assessment of Adolescent Coping: It's a Complicated Process. (1st October 2019) - Duvenage, Megan; Uink, Bep N.; Zimmer‐Gembeck, Melanie J.; Barber, Bonnie L.; Donovan, Caroline L.; Modecki, Kathryn L.
Abstract : Scholars have long‐called for researchers to treat coping as a process that is measured over an arc of time. Ambulatory assessment (AA) offers an appealing tool for capturing the dynamic process of adolescent coping. However, challenges in capturing the coping process are not altogether circumvented with AA designs. We conducted a scoping review of the AA literature on adolescent coping and draw from 60 studies to provide an overview of the field. We provide critiques of different AA approaches and highlight benefits and costs associated with various types of measurement within AA. We also speak to considerations of participant burden and compliance. We conclude with recommendations for developmental scholars seeking to deploy AA to capture this quintessential process among adolescents.